Wartość cierpienia w wielkopostnych wizjach Sługi Bożej Wandy Malczewskiej - Tatar, Marek (Warszawskie Studia Teologiczne, 2024)
A study of Wanda Malczewska’s writings makes it particularly possible to distinguish these that are accounts of her visions that she experienced during the Fridays of Lent in 1872. We note that they are very elaborate with many of her personal elements that go beyond the biblical texts. However, it is undoubtedly to be said that the very vivid images of the visions reveal the quite realistic character of Christ’s sufferings and also of the mystic participating in His entire Passion journey. Her identification with all the events deserves to be emphasised. She appears in them as a participant but also as a witness. She participates in this redemptive suffering of Christ, which is physical, psychological and spiritual suffering. A picture of dialogue in and through suffering emerges from the vision. The variety of categories of suffering also reveals its characteristics: redemptive, expiatory, compensatory, liberating. We can therefore conclude that the correct reading of suffering and its meaning for man and the world derives from its foundations and motives. This makes it not a suffering in which man focuses his attention on himself but leads to supernatural fruits. It is therefore not a question of glorifying it, but of stating that this attribute inherent in human life on the grounds of faith, hope and love becomes the possibility of an enlightening union with God. We are thus dealing with the experience of what we call felix culpa.